Active wall conditioning through boron powder injection compatible ELM control in EAST. (March 2023) - Xu, W.; Sun, Z.; Maingi, R.; Zuo, G.Z.; Yu, Y.W.; Li, C.L.; Guan, Y.H.; Zhou, Z.T.; Meng, X.C.; Huang, M.; Zhang, L.; Gao, W.; et al.
Highlights: The real-time boron injection effectively conditioned the plasma-facing components, as shown by the reductions in low-Z and high-Z impurities and the global recycling level in the whole inner vessel. The improved wall conditions resulted in suppression of strong MHD and an earlier transition from L- to H-mode. The boron powder injection shows effectively ELM control in H-mode discharges in the lower single null configuration with ion grad-B drift toward X-points while leaving the plasma density and stored energy largely unaffected. Abstract: Real-time wall conditioning and edge-localized mode (ELM) suppression through real-time boron powder injection into high-confinement mode discharges of the Experimental Advanced Superconducting Tokamak (EAST) have been investigated. The boron powder injection effectively conditioned the plasma-facing components, as shown by the reductions in low-Z and high-Z impurities and the global recycling level in the whole inner vessel, and suppressed the strong magnetohydrodynamic (MHD) activity in the plasma core. The improved wall conditions also resulted in an earlier transition from L- to H-mode. Boron powder injection also effectively suppressed ELM in the lower single null configuration with B T in the favorable direction while leaving the plasma density and stored energy largely unaffected.